Psycholinguistic and socioemotional characteristics of young offenders: Do language abilities and gender matter?. (5th April 2019) - Winstanley, Maxine; Webb, Roger T.; Conti‐Ramsden, Gina
Abstract : Purpose: Previous research demonstrates an association between developmental language disorder (DLD) and criminal offending. International research also implicates alexithymia as being over‐represented in forensic samples. This study provides a comprehensive examination of the psycholinguistic and socioemotional profiles of males and females in the youth justice system, with a focus on first‐time entrants. In the context of restorative justice (RJ) underpinning youth justice disposals, this allows for informed intervention and identifies those who may be compromised in their ability to effectively engage in certain interventions. Methods: Participants ( N  = 145) from a triage centre and youth offending teams, with a mean age of 15.8, completed a range of standardized psycholinguistic assessments considering non‐verbal IQ, expressive and receptive language measures, and literacy. Additionally, socioemotional measures completed included The Alexithymia Scale and the Strengths and Difficulties Questionnaire. Results: Developmental language disorder was present in 87 participants. Except for the emotional score, no statistically significant gender differences were found. The mean language scores for the DLD group were more than 2.25 standard deviations below the normative mean, and they demonstrated greater literacy difficulties. A high proportion of the group met the criteria for alexithymia/possible alexithymia (60%), and this was not associated with DLD. Conclusions: High prevalence values for DLD and socioemotional difficulties, not generally gender‐specific, were found. These difficulties have the possibility to compromise a young person's ability to engage in rehabilitative strategies. Language assessment and identification of difficulties, especially DLD, upon entry to the youth justice service, would assist when planning interventions.